Analysis of Organizational Culture towards Organizational Change – Myth or Science?: Is the Organizational Culture of the Management Student Association (HMM) of Muhammadiyah Bandung University Forever? - Aghnia Yasyfa; Anisa Roshy Rosdian; Hesti Hisani Latifah Hamdah; Sofa Parihah Nurasiah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
ABSTRACT Organizational culture is often assumed to be fixed and resistant to change (the "myth" view), whereas the "science" perspective argues it can be deliberately shaped. This study examines this debate through a qualitative case study of the Management Student Association (HMM) at Universitas Muhammadiyah Bandung, analyzing whether its culture evolved across leadership periods. Data were collected through in-depth interviews and direct observation. Culture was examined through seven dimensions adapted from Robbins and Judge, while organizational change was analyzed using Kurt Lewin’s three-stage model (unfreezing, movement, refreezing). The findings indicate that HMM UMB's culture is dynamic rather than static: fundamental, constitutional-level values and rules are maintained consistently, while technical work systems, communication patterns, and operational structures adapt to each leadership style and organizational needs. All three stages of Lewin’s model were identifiable in the 2025–2026 transition, indicating that cultural change occurred through a deliberate process rather than by chance. These findings support the science perspective over the myth of an unchanging culture, offering practical implications for how student organizations can preserve their core identity while remaining adaptive to generational change.